La población ocupada según categoría de ocupación y condición de pobreza en el Perú periodo 2019-2023 - Vásquez Acosta, James Iván (2025)
Income insecurity directly affects people's spending capacity, forcing them to live in poverty or extreme poverty, as the case may be. Income, in turn, depends on the job skills individuals acquire, as a result of training, or the experience gained over the years. This master's thesis aims to analyze the occupational category in which workers considered to be poor have been working during the 2019–2023 period. For this reason, this descriptive thesis with a non-experimental design was carried out. The conclusions reached reveal that the poor population immersed in the labor market works as self employed workers (45.52%). Similarly, workers segmented as living in extreme poverty also work in the same occupational category: self-employed workers (49.43%). The analysis of workers considered non-extremely poor reveals that they also work as non-extremely poor, as 44.70% do so. A significant finding can be seen in the occupational categorization of non-poor workers, given that the vast majority of them work as wage earners, with 46.47% of them falling into this category. They are subordinate to the employer and comply with the employer's requirements.